2008
DOI: 10.5194/sd-6-43-2008
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Minimum Principal Stress from an Extended Leak-off Test Onboard the <i>Chikyu</i> Drilling Vessel and Suggestions for Future Test Procedures

Abstract: No abstract available. <br><br> doi:<a href="http://dx.doi.org/10.2204/iodp.sd.6.06.2008" target="_blank">10.2204/iodp.sd.6.06.2008</a>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(4 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The basic steps to perform FSTs are described as follows: Conduct a casing integrity test (CIT) before drilling the casing shoe to ensure the integrity of the casing. Drill 10–20 feet below the casing shoe and circulate the mud to condition it. Pull the drill bit back into the casing to prevent the downhole assembly from sticking during the test. Connect the cement unit to the drill pipe and/or annulus and close the rams around the drill pipe. Start pumping mud into the isolated system while recording the pressure and the volume of mud that is pumped until the target test pressure is reached. …”
Section: Hoop Stresses In the Wellborementioning
confidence: 99%
See 1 more Smart Citation
“…The basic steps to perform FSTs are described as follows: Conduct a casing integrity test (CIT) before drilling the casing shoe to ensure the integrity of the casing. Drill 10–20 feet below the casing shoe and circulate the mud to condition it. Pull the drill bit back into the casing to prevent the downhole assembly from sticking during the test. Connect the cement unit to the drill pipe and/or annulus and close the rams around the drill pipe. Start pumping mud into the isolated system while recording the pressure and the volume of mud that is pumped until the target test pressure is reached. …”
Section: Hoop Stresses In the Wellborementioning
confidence: 99%
“…The basic steps to perform FSTs are described as follows: 7 Conduct a casing integrity test (CIT) before drilling the casing shoe to ensure the integrity of the casing. Drill 10–20 feet below the casing shoe and circulate the mud to condition it.…”
Section: Hoop Stresses In the Wellborementioning
confidence: 99%
“…Determining in situ stress at depth is required in different programs, especially in hydraulic fracturing and drilling operations. In this regard, LOT and XLOT data can be used for estimating the magnitude of the in situ minimum principal stress at depth [51][52][53]. Addis et al, for the first time, compared the LOT and XLOT results in the North West Shelf of Australia and the Norwegian North Sea and concluded that the XLOT results were more consistent than LOTs and despite consuming longer time, obtained much preferable data than LOT and recommended XLOT tests where stress data are needed [21].…”
Section: Lot/xlot Application In In-situ Stress Estimation and Geomec...mentioning
confidence: 99%
“…The vertical stress S v is typically computed by integrating over the density log from the surface to a predetermined depth. The minimum horizontal stress, S hmin , is estimated from pressure monitoring during hydraulic fracturing tests (if they propagate perpendicular to S hmin ) performed in isolated intervals (Fairhurst, 2003;Lin et al, 2008;Ljunggren et al, 2003;Schmitt et al, 2012). However, estimation of the maximum principal stress S hmax is somewhat challenging and associated with a significant amount of uncertainty.…”
Section: In Situ Stress Characterizationmentioning
confidence: 99%